FAULT SEAL ANALYIS IN SEPINGGAN DELTAIC SEQUENCE INTERVAL, JM FIELD, SOUTH MAHAKAM, KUTAI BASIN - SEPTIANSYAH ( NIM: 22015025), FERDY
JM field was discovered in 1990 by drilling of well exploration on the upthrown block of Metulang fault and in 1996 on the downthrown block. From the drilling result of the both blocks were known that in the downthrown block had the largest hydrocarbon accumulation. The differences of hydrocarbon accumulation from the both blocks are interpreted due to there is fault seal in the Metulang fault. The difference of it have given more influences to the JM field development. Therefore, the understanding of comprehensive fault seal system of metulang fault is needed to field development in the future. The approaching methodology of this study is static analysis method using SGR parameter (shale gouge ratio) with the objective is to know characteristic of Metulang fault seal and also its the controlling factor. Structural style in JM field is transtensional with negative flower structure. This structural style was controlled by sepinggan strike slip (dextral) fault system. Metulang fault as the object of this study is a product of that structural style and it faults was predicted active from periode pre middle mioecene (pre MF12) until late middle miocene (U9.5). Metulang fault seal has characteristic as follows: SGR maximum threshold 0.40 (leaking), maximum capillary pressure threshold ± 18.4 bar and minimum ± 4 bar, permeability threshold for fluid to flow ± 0.064 md, juxtaposition type is tend to fully juxtaposed that dominated by extrareservoir faults, throw maximum is ± 160 meters and throw minimum is ± 7.44 meters. The differences of hydrocarbon accumulation between upthrown and downthrown blocks are surely due to there is Metulang fault seal. It is proven by juxtaposition between reservoir with non reservoir and also reservoir with reservoir that influenced by membrane seal. Based on the datas and the facts, it can be concluded that the controlling factor of Metulang fault seal are more on the content of Volume shale rather than the throw of the Metulang fault